Core-shell magnetic CFO@COF composites toward peroxymonosulfate activation for degradation of sulfamethoxazole from aqueous solution: A comparative study and mechanistic consideration. (January 2023) - Su, Chenxin; Jia, Muhan; Xue, Xiaofei; Tang, Chenliu; Li, Lingyun; Hu, Xiang
Abstract: A core-shell covalent organic framework encapsulated Co1.2 Fe1. 8 O4 magnetic particles (CFO@COF) was designed and prepared successfully to activate peroxymonosulfate (PMS) for sulfamethoxazole (SMX) degradation. It displays amazing catalytic reactivity since the unique interior structure and synergistic effect between COF shell and CFO core, reaching 99.8% removal of SMX (10 mg/L) within 30 min and 90.8% TOC removal. The synergy between bimetals vests high reactivity to CFO core. And the outer COF shell can stabilize the CFO core under intricate reaction conditions to restrain the leaching of Co ions (decreased from 0.75 to 0.25 mg/L). Further investigation compared the activation mechanism in two different system, CFO/PMS system and CFO@COF/PMS system. The result showed that the radical mechanism controlled by SO4 ⋅- guided the SMX degradation in CFO/PMS system whereas the 1 O2 played a pivotal role in CFO@COF/PMS system called non-radical leading. The influences of various factors on degradation experiments and SMX degradation pathway were also studied. Most importantly, risk assessment in CFO@COF/PMS/SMX system was estimated via "ecological structure activity relationships". In most case, the toxicities of intermediates were lower than the initial samples, which confirmed the effectiveness of CFO@COF/PMS/SMX system in the reduction of toxicity of SMX. Graphical abstract: Image 1 Highlights: Core-shell CFO@COF was successfully synthetized via hydrothermal method. The outer COF shell significantly improve the leaching problem of Co ions. Different mechanisms of CFO and CFO@COF activated PMS were summarized. Risk assessment in CFO@COF/PMS/SMX system were estimated via ECOSAR.